The Influence of Anxiety on the Learning Outcomes of Grade 5 Students at SDN 62 Rontu, Bima City - Ernawati, Ernawati; Hardiningsih, Sri; Cahyadi, Anggi Tri (FKIP - Universitas Riau, 2025)
Anxiety is a feeling of discomfort, tension, or worry that arises without a clear cause. This study aims to determine the influence of anxiety on the learning outcomes of 5th-grade students at SDN 62 Rontu in Bima City. The research method used is qualitative, employing interviews, observations, and documentation techniques. The subjects of the study are students who exhibit signs of anxiety while learning. The results show that students experience physical symptoms such as palpitations, sweating, and general discomfort, as well as psychological symptoms like difficulty concentrating and being easily forgetful. Students also demonstrate negative attitudes, such as low self-confidence and increased anxiety. This anxiety leads to decreased participation and academic achievement. Factors causing anxiety include pressure from teachers, assignments, exams, and a lack of support from family and peers. In conclusion, anxiety has a negative effect on learning outcomes. Therefore, the roles of teachers and parents are essential in creating a supportive and comfortable learning environment.